Psychosocial factors influencing the frequency of fast-food consumption among urban and rural Costa Rican adolescents - Monge Rojas, Rafael (2013)
Objective: The aim of this study was to identify psychosocial factors that influence fast-food consumption in urban and rural Costa Rican adolescents. Methods: A self-administered questionnaire designed for the study asked about sociodemographic information, frequency of fast-food consumption, meaning of “fast food,” location of purchase, and psychosocial correlates. Five psychosocial factors were extracted by using principal components analysis with Varimax rotation method and eigenvalues. Descriptive statistics and a hierarchical linear regression model were used to predict the frequency of fast-food consumption. Results: Responses from 400 adolescents (ages 12–17 y) reveal that daily consumption of fast food was 1.8 times more frequently mentioned by rural adolescents compared with urban youth. Urban and rural differences were found in the way adolescents classified fast foods (rural adolescents included more traditional foods like chips, sandwiches, and Casadoda dish consisting of rice, black beans, plantains, salad, and a meat), and in purchasing locations (rural adolescents identified neighborhood convenience stores as fast-food restaurants). Living in rural areas, convenience and availability of foods, and the presence of external loci of control were predictors of a higher frequency of fast-food consumption, whereas health awareness predicted a lower frequency. Conclusions: The development of interventions to reduce fast-food consumption in Costa Rican adolescents should consider not only convenience, but also the availability of these foods where adolescents are more exposed, particularly in rural areas. Interventions such as improving the convenience of healthy fast foods available in school canteens and neighborhood stores, policies to increase the price of unhealthy fast food, and activities to provide adolescents with the skills to increase self-efficacy and reduce the effect of external loci of control are recommended.